An efficient symmetric searchable encryption scheme for dynamic dataset in cloud computing paradigms. (2018) - Zhao, Minghao; Jiang, Han; Li, Zhen; Xu, Qiuliang; Wang, Hao; Li, Shaojing
Searchable encryption is a significant cryptographic primitive to ensure storage security and data privacy in cloud computing environment. It allows a client to store a collection of encrypted documents on server, and latterly, according to specific search criteria, perform keyword-based searches and retrieve the documents, meanwhile ensuring that it reveals minimal information to the server. Early research on searchable encryption schemes mainly focused on the efficiency, the security and the query expressiveness, and nowadays, the studies have been paying attention to searchable encryption that supports dataset update dynamically. In this paper, we propose a new dynamic symmetric searchable encryption scheme. In the aspect of efficiency, the complexity of search algorithm is O (1), while file addition and deletion are O ( m"n ) and O ( N ) respectively (here m" means the number of keywords in a document; N means the number of document-keyword pairs and n means the size of keywords dictionary), which indicates the overall efficiency is superior to the existing schemes; in terms of security, this scheme can resist selective keyword attack, and compared with former ones, it achieves less information leakage.